Hybridization as a form of conservation and genetical enhancement of the Arecaceae family: a review on the palm x Butyagrus paranaënsis Engels, T.A.Meyer & K.Soares nothsp. nov (Research, Society and Development, 2023)
The Arecaceae family is known for its economic and environmental importance, with wide worldwide distribution due to its adaptability to climatic and edaphic conditions, it is found in all Brazilian biomes, its population is threatened with extinction, mainly because of anthropic actions. This work consists of a narrative review, based on scientific publications on the Family and, more specifically, on the genera Butia (Becc.) Becc. and Syagrus Mart. Data were obtained from scientific literature in books, websites and digital magazines. A gathering of botanical and biogeographic characteristics of the aforementioned genera, with the objective of supporting research work on viable alternatives for the conservation and valorization of these palm trees. Having as a proposal the development of breeding techniques by hybridization, in obtaining commercially desirable responses and to implement proposals for the preservation of native palm trees. Seeking to emphasize the importance of palm trees both for ecosystems and for the economic development of communities in order to seek alternatives for their preservation.